Community Perceptions of The Challenges and Opportunities of Building an Eco-Industrial Park - Ma’rifah, Aula Nurul; Anita, Anita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to find out the community's perception of the challenges and opportunities of building an eco-industrial park. This research uses a qualitative approach with data collection methods through interviews. The sample of this research is in gen-Z with accidental sampling method so that a sample of 116 respondents was obtained. The results showed that some people understand the importance of maintaining ecological balance in various industrial activities in the hope of reducing waste. However, regarding the eco-industrial park (EIP), there are still people who do not fully understand the concept of EIP and how to implement it. The EIP concept provides the benefit of encouraging innovation and resource efficiency. Support from the government, industry, academics, researchers, and the general public is still needed in order to jointly build an industrial park with the EIP concept.